Review of test development and testing practices in the Republic of Croatia - Matešić, Krunoslav (2007)
By request of the editor of 'Testing International' the official publication of the International Test Commission, the author has written a review of test development and testing practices in Croatia, adhering to the given format of 1400 words.
Projekt MZOS
ENG